Membangun Prototype Aplikasi Pengendali Listrik Ruangan pada Gedung Berbasis Jaringan TCP/IP - Tri Daryanto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2009)
Computer Technology this time not merely utilized in just data processing. But the Computer technology canbe utilized controller some equipments, one of them is controller room electricity in the building used network,so that more efficient.Device of Application controller of this lamp use parallel port facility at computer and use method ofposition of bit of binary. This application can control electricity 12 rooms in the building and 2 building can becontrolled.Keywords: electricity, controller, port parallel and bit